Do Managers Do Good with Other People’s Money? - Cheng, Ing-Haw; Hong, Harrison; Shue, Kelly (The Review of Corporate Finance Studies, 2023)
Abstract There is mixed evidence on whether the marginal dollar spent on corporate social responsibility is due to agency problems. We propose an approach by modeling how the 2003 dividend tax cut, which increased after-tax insider ownership and better aligned managerial and shareholder interests, affected the marginal dollar spent on firm responsibility. We confirm key predictions of our agency model: following the tax cut, moderate insider-ownership firms experience larger declines in their responsibility ratings and increases in their valuations relative to other firms. We also confirm another implication regarding managerial misalignment using a regression-discontinuity design of close votes on shareholder-governance proposals. (JEL G30, G31, G35) Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.